2017
DOI: 10.1038/ijo.2017.286
|View full text |Cite
|
Sign up to set email alerts
|

Diet-resistant obesity is characterized by a distinct plasma proteomic signature and impaired muscle fiber metabolism

Abstract: Background/Objectives:Inter-individual variability in weight loss during obesity treatment is complex and poorly understood. Here we use whole body and tissue approaches to investigate fuel oxidation characteristics in skeletal muscle fibers, cells and distinct circulating protein biomarkers before and after a high fat meal (HFM) challenge in those who lost the most (obese diet-sensitive; ODS) vs the least (obese diet-resistant; ODR) amount of weight in a highly controlled weight management program.Subjects/Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…Following gel electrophoresis, we blotted membranes with antibodies against CI–V subunits. Interestingly, upon qualitative assessment, compared with our previously published BN-PAGE results (13, 37, 38), we found that CI- and CIII-containing subunits were often entirely associated with ETC supercomplexes in these cells ( Fig. 2 A ).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Following gel electrophoresis, we blotted membranes with antibodies against CI–V subunits. Interestingly, upon qualitative assessment, compared with our previously published BN-PAGE results (13, 37, 38), we found that CI- and CIII-containing subunits were often entirely associated with ETC supercomplexes in these cells ( Fig. 2 A ).…”
Section: Resultssupporting
confidence: 57%
“…S3B-D). Similar to some other mammalian cells and tissues (13,22,37,38), MSCs contained very little to no CV dimer under these experimental conditions.…”
Section: Mitochondrial Bioenergetics and Etc Supercomplexes Are Altersupporting
confidence: 67%
“…We therefore hypothesized that protein scanning could deliver comprehensive individualized health assessments-but with single-source convenience and greater usability in typical medical practice. While this approach using modified aptamers has gained provenance for discovering and understanding gene-protein interactions 1 , drug pharmacology 11 , biological control systems 2 , biomarkers in individual diseases and risks [3][4][5][6][7][8] , aging 9 and obesity 10 , it has not been evaluated previously as a potentially holistic, quantitative health assessment for simultaneous evaluation of multiple health issues.…”
mentioning
confidence: 99%
“…In contrast, the present study is based on a secondary analysis of what was primarily a weight loss diet study involving 609 generally healthy overweight or obese adults without diabetes, randomly assigned to healthy low-fat (HLF) or healthy low-carbohydrate (HLC) diet, in which we analyzed 263 plasma proteins using the Olink Proteomics arrays. Weight loss response in clinical obesity treatment programs is highly variable and we hypothesized that this heterogeneity can be characterized by a distinct plasma proteomic signature 16 . This may open up avenues for incorporation of protein biomarker measurements into weight loss prediction models to help individuals choose a diet for optimal weight loss.…”
mentioning
confidence: 99%